Animal remains in mortuary contexts in Southern Patagonia: A case study in lake Salitroso (Santa Cruz, Argentina) - Rindel, Diego Damián (2024)
The aim of this paper is to discuss the role of faunal remains in funerary contexts from Southern Patagonia. We will particularly emphasize the information obtained in mortuary contexts from Lake Salitroso (Santa Cruz Province, Argentina). In this area a total of 37 burials of different types, such as chenques (i.e. artificial rock burial mounds), burial under blocks and niches, have been studied. Results indicate low frequency of animal remains, mostly corresponding to fox (Lycalopex Burmeister, 1856) and guanaco (Lama guanicoe Müller, 1776). Additionally, certain variability in skeletal part representation has been detected. These characteristics are not reflected in the documentary sources of first European explorers in Patagonia, but are common in the regional archaeological record. Finally, another outcome of interest is the presence of animal remains deposited by natural processes (rodents, edentates and carnivores). The results are contextualized with available regional ethnohistoric and archaeological information to discuss the role of animal species in the funerary practices of hunter-gatherer populations in southern Patagonia.